Calicium chlorosporum new to Europe - Sarrión, Francisco J.; Tibell, Leif; Burgaz, Ana Rosa (Botanica Complutensis, 2007)
Calicium chlorosporum has been found for the first time in Europe. It was growing on wood of Abies pinsapo in southern Spain. The description of the taxa and related species as well as a world distributional map is provided.